Peran Strategis Non-Govermental Organization (NGO) dalam Krisis Pengungsi Vietnam Tahun 1979-1996 di Pulau Galang, Indonesia - Cosmas Eko Suharyanto; Suali Suali (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study analyzes the strategic role of non-governmental organizations (NGOs) in managing Indochinese refugees namely from Vietnam, Cambodia, and Laos on Galang Island during the period 1979–1996. The “boat people” crisis at that time required a multisectoral response that was not only emergency-based but also sustainable, linking Indonesia’s transit policies with applicable international protection standards. Using a literature review method of international journal articles and program technical documents, this study finds that NGOs performed crucial functions beyond mere logistical assistance, particularly through structured educational planning such as the Overseas Refugee Training Program (ORTP). Recent literature indicates that NGO consortia such as SCF and EIL, along with faith-based organizations such as JRS, YCK, and ICMC, played a significant role in fostering refugee self-reliance through cultural orientation curricula and work simulation programs (Work Orientation). Despite various structural challenges and resource limitations, the experience on Galang Island demonstrates the effectiveness of partnerships between NGOs and the government in supporting adaptive and sustainable regional humanitarian diplomacy.